1998
DOI: 10.1111/j.1151-2916.1998.tb02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Hot Isostatically Pressed SiC‐AIN Powder Mixtures: Effect of Milling on Solid‐Solution Formation and Related Properties

Abstract: Powder mixtures with nominal compositions of 75 mol% SiC and 25 mol% AlN as well as 50 mol% SiC and 50 mol% AlN were prepared by ball milling for 1-300 h and subsequently sintered to full density by hot isostatic pressing (HIPing) at 1850°C under a pressure of 200 MPa. Microstructures and properties of the HIP-sintered SiC-AlN powder mixtures were investigated with special attention to the effect of ball milling on the formation of SiC-AlN solid solutions. Extensive ball milling facilitated effectively the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…An increase in the contact area among the particles always shortens the diffusion paths of reactants. The previous studies have also indicated that the higher contact area among reactants as well as the finer reactant particles leads to the lower transformation temperature of AlN and SiC into AlN–SiCss …”
Section: Resultsmentioning
confidence: 95%
“…An increase in the contact area among the particles always shortens the diffusion paths of reactants. The previous studies have also indicated that the higher contact area among reactants as well as the finer reactant particles leads to the lower transformation temperature of AlN and SiC into AlN–SiCss …”
Section: Resultsmentioning
confidence: 95%
“…Previously, Li et al 2 found sluggish interdiffusion between AlN and SiC and stressed some requirements for forming the solid solution with a homogeneous composition, i.e., small starting particle size (e.g., below 0.5 m at 1850°C) and thorough mixing of the starting powder. These requirements are met by the present technique.…”
Section: Resultsmentioning
confidence: 99%
“…These AlN-SiC ceramics form a solid solution over a wide chemical compositional range, 1 which is rather rare for non-oxide ceramics with strong covalent bonds. 2 The homogeneous formation of solid solution helps enhance the mechanical properties, chiefly due to the restriction of excessive grain growth. For example, the formation of homogeneous solid solution increases flexural strength and fracture toughness of the ceramics up to 1 GPa at 65-75 mass% of SiC and 4.5-5 MPa⅐m 1/2 at 90 mass% SiC, respectively, 3,4 whereas that of poor solid solution shows lower mechanical strengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that AlN could form solid solution with SiC and affected the structural stability of SiC [12]. Some researchers have revealed that SiC with the addition of AlN could be preferably sintered by hot pressing [13][14][15] or spark plasma sintering [11] or hot isostatic pressing [16], and densification in such system was frequently explained by AlN going into solid solution in SiC in a large proportion. As for pressureless sintering with AlN, Malinge et al [17] found that the added AlN had almost no influences on the density of SiC ceramics which contain boron carbide and carbon.…”
Section: Introductionmentioning
confidence: 99%